2022
DOI: 10.1038/s41598-022-21666-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for globe removal after open-globe injury in agricultural regions

Abstract: This study aimed to identify the prevalence and risk factors for globe removal among patients with open-globe injuries (OGIs) in agricultural regions. A retrospective chart review of patients with OGIs was performed between January 2010 and December 2019. Univariable and multivariable logistic regression models were used to identify the factors associated with globe removal in OGI. This study included 422 patients (422 eyes). The highest prevalence of OGI was observed in the middle age group (> 20 to 40 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Research has shown that the vast majority of eye injuries, whether in adults or children, are preventable [ 12 – 14 ]. Therefore, particular attention should be paid to the prevention of eye injuries in occupations prone to ocular trauma such as farming, and in children [ 8 , 15 , 16 ]. Studying the biomechanics of OGI and its influencing factors can provide information useful for the evaluation of OGI risk and for prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that the vast majority of eye injuries, whether in adults or children, are preventable [ 12 – 14 ]. Therefore, particular attention should be paid to the prevention of eye injuries in occupations prone to ocular trauma such as farming, and in children [ 8 , 15 , 16 ]. Studying the biomechanics of OGI and its influencing factors can provide information useful for the evaluation of OGI risk and for prevention.…”
Section: Introductionmentioning
confidence: 99%